FRI0035 Disease remission is more common but less stringent in anti-citrullinated protein antibody-positive patients with early rheumatoid arthritis treated with conventional synthetic disease modifying drugs. (12th June 2018) - Manzo, A.; Bugatti, S.; Zanframundo, G.; Benaglio, F.; Sakellariou, G.; Montecucco, C.; Caporali, R.
Abstract : Background: Early diagnosis and goal-steered treatment strategies allow the achievement of disease remission in a significant proportion of patients with early rheumatoid arthritis (RA). Autoantibodies such as anti-citrullinated protein autoantibodies (ACPA) identify a subset of patients with a common pathogenetic background and more severe course of the disease. However, whether autoantibodies also impact the response to conventional synthetic disease modifying anti-rheumatic drugs (csDMARDs) remains object of debate. Objectives: To investigate the frequency and the characteristics of disease remission in relation to the autoantibody status in patients with early RA treated with csDMARDs. Methods: The study population consisted of 578 early RA patients (<12 months of symptoms) consecutively recruited at our Early Arthritis Clinic, treatment-naïve at inclusion and prospectively followed-up at regular intervals upon initiation of therapy with methotrexate (MTX) aimed at the achievement of low disease activity (28-joints disease activity score [DAS28]≤3.2). ACPA and rheumatoid factor (RF) were centrally determined on baseline sera. The frequency of remission according to the DAS28 (<2.6) and to the simplified disease activity index (SDAI ≤3.3) over the first 12 months stratified by the autoantibody status was assessed by Cox regression. The following characteristics were further analysed: time to remission, swollen and tender joint count, and acute phase reactants at remission. Results: 533/578 (92.2%) patients completed a follow-up of at least 12 months. Patients fulfilled the 2010 classification criteria for RA (81% also fulfilled the 1987 criteria) and had short disease duration at inclusion (median [IQR] 15.6 [9.4–27.8] weeks). Collectively, 53.9% and 44% of the patients achieved DAS28 and SDAI remission, respectively, at least once over the first 12 months of treatment. After adjusting for age, gender, symptoms' duration, baseline disease activity, MTX starting dose and prednisone co-medication, ACPA positivity was associated with slightly increased hazards of achieving both DAS28 (HR [95% CI] 1.24 [1.01–1.63]) and SDAI remission (HR [95% CI] 1.36 [1.01–1.85]) (figure 1A, B ). However, irrespective of the remission criterion, ACPA-positive patients had higher numbers of residual swollen joints while being in remission, particularly in association with high levels of RF (>3 ULN) (figure 1C, D ). Furthermore, remission was delayed in RF-high ACPA-positive patients compared to RF-low (figure 1E, F ). Other features such as joint tenderness and acute phase reactants did not show significant differences among different serological subgroups. Conclusions: Early diagnosis and initial treatment with MTX result in high remission percentages in RA patients regardless of autoantibody positivity. However, remission appears less stringent in ACPA-positive patients, particularly when RF is also high. These findings indicate that current treatment approaches may be insufficient at effectively suppressing joint inflammation in autoantibody-positive patients. Disclosure of Interest: None declared